Effect of Trolox addition as antioxidant in refrigeration medium in porcine spermatozoa - Camporino, A. (2022)
The aim of this study was to analyze the effect of Trolox addition to semen diluents on porcine sperm refrigeration evaluated by functional tests in order to predict their potential fertilization capacity and to increase the knowledge regarding their quality parameters and refrigeration conditions to optimize porcine sperm conservation. A 200 µM Trolox concentration was added to a pool of boar semen samples diluted in Modena modified medium and stored at 17 °C. At days 1, 2 and 5 postrefrigeration, sperm motility, viability and acrosome integrity, pre-capacitation state, plasma membrane function and mitochondrial membrane potential were evaluated. In conclusion, the addition of 200 µM Trolox to seminal samples in the porcine species produced a significant increase in the preservation of plasma membrane functionality at day 1 and 5 compared with untreated samples. An increase in progressive motility evaluated by light microscopy was also observed on day 1 in treated samples compared to untreated samples. No significant differences were observed in vitality, mitochondrial membrane potential and pre-capacitation patterns between treated and untreated samples throughout the refrigeration time.